Analisis Epistimologi Zakat dalam Perspektif Fiqih - Hamdan Ladiku (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2020)
This study aims to analyze the epistemology of zakat in the perspective of fiqh. The reality of Muslims shows an imbalance between the awareness of tithe and the understanding of zakat fiqh. so the vision of zakat changing mustahik into muzakki cannot be optimized. The method used is library research, with qualitative descriptive analysis techniques. The results showed that zakat was intended as "settlement". Zakat is required by Allah to be given to those who are entitled. The texts of the commands of zakat are analyzed through the linguistic approach of the Qur’an displaying them in three language styles (uslứb), namely: Using uslub insyâi, which is mandatory. Using the uslub tarhib (warning) aimed at people who like to accumulate wealth and do not want to pay zakat. Using uslub madh (praise/adulation) is God's praise for those who pay zakat. Philosophically, humanity is positioned into two groups, namely rich and poor, as a framework for God's plan to create a harmonious balance in realizing true justice and educating people to behave and behave fairly (ummatan wasatan).